Impact of international offshoring on the labour market. A reflection on the conceptual and methodological aspects. - Luengo Escalonilla, Fernando; Álvarez Peralta, Ignacio (Papeles de Europa, 2009)
The objective of this paper is to analyse the conceptual and methodological aspects of international offshoring (IO) and its impact on the labour market. This paper presents therefore two necessarily complementary levels. On the one hand, the more general one, which aims to pinpoint the conceptual keys of the offshoring dynamic; on the other hand, we review different instruments and approaches, in order to measure this phenomenon and to evaluate its impact on the labour market. We first ascertain a brief conceptual demarcation of international offshoring. After that, we examine different methodological tools in order to measure international offshoring and the impact of IO’s on the labour market. The implications of IO for the labour market -complex, diverse and not always easy to establish– depend on a series of factors which must be considered simultaneously: the magnitude of the process, its characteristics, the underlying causes and the strategies and responses generated by economic, social and institutional agents. All of these aspects will be addressed –from a conceptual and methodological point of view- in different sections of the present paper.